ANALISIS MISKONSEPSI PESERTA DIDIK DALAM MENYELESAIKAN SOAL CERITA SPLTV BERDASARKAN TEORI NOLTING - Nurul Santi Kalsum -; Syahruni Tri Handayani; Nurannisa Awalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to analyze and describe various problems faced by students in solving story problems related to SPLTV material, as well as to identify the factors that cause them. This study uses a qualitative descriptive approach, where the research subjects are three students of grade XI at MA As'adiyah Sei. Nyamuk. The instrument used in this study is a written test in the form of story problems. The results of this test become the basis for data collection. Data analysis is carried out using qualitative methods through the stages of data condensation, analysis, and evaluation. This study aims to improve students' ability to solve contextual problems, especially those related to mathematics. Based on the results of the study, it was found that there are four types of errors made by students in solving SPLTV story problems based on Nolting's Theory. The most dominant types of errors are omission errors and conceptual errors, each amounting to 37.50%. In general, the causes of these errors are a lack of understanding of the mathematical material and a lack of accuracy in solving problems. Solutions that can be done to overcome this problem are to deepen the understanding of mathematical concepts through various trusted learning sources and increase practice in solving story problems.